The eye of the team : critical incidents analysis of team metaphors used by teams in a health setting : a thesis submitted in partial fulfillment of the requirements for the degree of Master of Arts in Psychology at Massey University - Ramkissoon, Vinodhini (Massey University, 2005)
This study sought to explore working teams' mental models of their success and failure, to cast light on what improves rather than undermines the teams' performance. Implicit team mental models may become explicit through exploring the language, specifically metaphors, that teams use to describe successful and unsuccessful performance. Ten teams comprising 69 individuals from a large district health board and including one all Māori team, participated in semi-structured interviews, that focused on the positive and negative critical incidents, when working together. Twin Content analyses of each type of incident revealed classical attribution biases, for example self-serving biases (team failures externalised using system metaphors as in "It is not our fault, it is the computer's fault" and successes internalised as in "the high standard of work is a reflection on the integrity and skills of the team"). At the same time however teams occasionally sidestepped these biases by reflecting on whether they could have achieved even more. Unlike their counterparts, the single all-Māori team used the same "two worlds" metaphor to describe both success and failure through bi-cultural harmony and bi-cultural conflict. Discussion focuses on how metaphors enhance team development. For example through discourse analysis of training sessions, teams may become aware of what biases the team is engaging in, thereby fuelling organisational learning.
Keywords: New Zealand; Teams in the workplace; Organisational behaviour; Metaphor; Social aspects